Best practices in the laboratory diagnosis, prognostication, prediction, and monitoring of Graves’ disease: role of TRAbs - Sanjay Kalra; Shahjada Selim; Dina Shrestha; Noel Somasundaram; Syed Abbas Raza; Manash P. Baruah; Saptarshi Bhattacharya; Sharvil Gadve; Ganapathi Bantwal; Rakesh Sahay (BMC Endocrine Disorders)
Abstract Graves' disease (GD) is an autoimmune disorder characterized by activation of the TSH receptor by stimulatory autoantibodies (TSH Receptor Antibodies, or TRAbs), leading to unregulated thyroid hormone production. Diagnosis is largely based on the typical clinical picture and laboratory thyroid panel. Establishment of elevated serum levels of TRAbs by competitive binding assay or cell-binding assay has its unique role in diagnosis and management of GD, especially in the differential diagnosis, therapy selection, prognostication, evaluation of thyroid function during pregnancy, peri-conceptional and neonatal thyroid workup, and in certain special situation. Inclusion of TRAbs in GD diagnostic algorithm can improve cost-effectiveness of GD management. The current best practice guidelines were developed to provide evidence-based recommendations in the use of TRABs in GD management for healthcare providers in South Asia. A panel of endocrinologists with minimum 10 years of clinical experience in thyroid disorders reviewed existing literature and their quality, and after deliberation and discussion, developed 21 recommendations surrounding the best practices surrounding the role of TRAbs in GD management.